The impact of developmental genes in non-syndromic cleft lip and/or palate - Şahin Uysal, Nihal; Şahin, Feride İffet; Terzi, Yunus Kasım (Journal of the Turkish German Gynecological Association, 2023)
Non-syndromic cleft lip and/or palate (NSCL/P) is a congenital malformation with a prevalence of 1:700 births. It has a multifactorial etiology. Human craniofacial development takes place during the first 10 weeks of pregnancy. Normal craniofacial development arises from the convergence and fusion of the facial and palatal processes and involves interactions between genes that regulate cell growth, proliferation, differentiation, epithelial-to-mesenchymal transition, and apoptosis. Whole genome/exome analysis, and also genome-wide association studies give us to chance to identify the genetic factors which contribute to the development of NSCL/P. After detecting a cleft lip and/or palate on ultrasonography without associated anomalies, the patient should be evaluated in collaboration with a clinical geneticist, taking into account the many genes and environmental factors involved in NSCL/P etiopathogenesis, and a roadmap for possible genetic diagnosis should be drawn.